The E3 ubiquitin ligase RNF135 regulates the tumorigenesis activity of tongue cancer SCC25 cells - Jian Jin; liya Zhao; Zubing Li (Cancer Medicine, 2016)
Abstract Several E3 ubiquitin ligases have been confirmed that they are related to the tumorigenesis. This study aims to find the tongue cancer‐related E3 ubiquitin ligase. The E3 ubiquitin ligase library was screened. The effect of candidate molecule on tongue cancer was validated through cell viability, cell proliferation, colony formation, invasive assay in vitro, and the xenograft model in vivo. The E3 ubiquitin ligase RNF135 significantly promoted the expression of PTEN and TP53 in SCC25 cells. The overexpression of RNF135 inhibited the viability, proliferation, and invasion of SCC25 cells. Knockdown of RNF135 had the opposite effects. Furthermore, RNF135 regulates the tumorigenesis activity of SCC25 cells in vivo. Our results demonstrated that RNF135 had the potential to affect the development of the tongue cancer in vitro. The further in vivo study is helpful to fully understand the role of it.